The effect of sulfonated poly (ether ether ketone) as the electrode ionomer for self-humidifying nanocomposite proton exchange membrane fuel cells. (15th March 2015) - Rahnavard, Aylin; Rowshanzamir, Soosan; Parnian, Mohammad Javad; Amirkhanlou, Gholam Reza
Abstract: As the electrode ionomer is a key component of the catalyst layer, the introduction of new electrode ionomer would have a significant effect on cell performance. In addition, the content of ionomer in the catalyst electrodes is one of the most important factors to determine Pt catalyst utilization. In this study, SPEEK (sulfonated poly ether ether ketone) was used as ionomer in the electrodes, and the influence of different ionomer content (15, 25 and 35 wt. %) on the electrodes was investigated. Furthermore, different content of platinum (0.3, 0.4 and 0.5 mg. cm −2 ) was used for the electrode preparation. The degree of sulfonation of SPEEK was determined about 66%. RSM (response surface methodology) was used to arrange the experiments. CV (cyclic voltammetry) experiments were performed to calculate EPSA (electrode platinum surface area) and Pt catalyst utilization. The cyclic voltammetry experiments showed the best result in 25% of ionomer with 0.5 mg. cm −2 of platinum. MEAs (membrane electrode assemblies) were made with the optimum platinum content (0.5 mg. cm −2 ) and self-humidifying nanocomposite membrane (SPEEK/Pt–Cs2.5 H0.5 PW12 O40 ) for polarization test. The catalyst layer with 25 wt.% of SPEEK ionomer and 0.5 mg. cm −2 of platinum showed the best I–V result which is in agreement with the CV results. Highlights: Sulfonated poly ether ether ketone (SPEEK) was used as ionomer in the electrodes. Different content of platinum was used for the electrode preparation. Different ionomer content on the electrodes was investigated. The CV experiments showed the best result in 25% of ionomer with 0.5 mg.cm −2 of Pt. The catalyst layer with 25% of ionomer and 0.5 mg.cm −2 of Pt showed the best I–V result.